2014
DOI: 10.1007/s10753-014-9899-9
|View full text |Cite
|
Sign up to set email alerts
|

Orientin Inhibits HMGB1-Induced Inflammatory Responses in HUVECs and in Murine Polymicrobial Sepsis

Abstract: High mobility group box-1 (HMGB1) protein acts as a late mediator of severe vascular inflammatory conditions. Orientin has been known to have anxiolytic and antioxidative activities. However, the effect of orientin on HMGB1-induced inflammatory response has not been studied. We assessed this question by monitoring the effects of post-treatment orientin and its derivatives on lipopolysaccharide (LPS) and cecal ligation and puncture (CLP)-mediated release of HMGB1 and HMGB1-mediated regulation of pro-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Several recent studies have demonstrated that orientin exerts a variety of pharmacological effects, including antioxidant, anti-inflammatory, and neuroprotective effects [24,25]. For example, orientin (20 mg/kg and 40 mg/kg, intragastric administration) has shown significant antioxidant properties in improving the neuronal ultrastructure in the hippocampus of D-galactose-aged mice [26].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have demonstrated that orientin exerts a variety of pharmacological effects, including antioxidant, anti-inflammatory, and neuroprotective effects [24,25]. For example, orientin (20 mg/kg and 40 mg/kg, intragastric administration) has shown significant antioxidant properties in improving the neuronal ultrastructure in the hippocampus of D-galactose-aged mice [26].…”
Section: Introductionmentioning
confidence: 99%
“…1) are compounds found in C. subternata, which is a plant traditionally used for the production of the South African herbal tea called honeybush, and recently as aqueous extracts for the food industry (Joubert et al 2011). Flavonoids such as saponarin (Seo et al 2014), orientin, isoorientin (Lee et al 2014a;Yoo et al 2014), vitexin (Borghi et al 2013), and isovitexin (Lin et al 2005) are structural analogues of VCN or SCL with significant antiinflammatory properties. Therefore, in this study, we examined the anti-inflammatory responses of VCN and SCL on the release of HMGB1 and HMGB1-mediated vascular barrier disruptive responses in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its antioxidant activity, orientin protects human erythrocytes in vitro from oxidative damage by attenuating oxidative stress; it protects antioxidative enzyme activities and preserves the integrity of the erythrocyte structure [31]. In an in vitro and in vivo study, antiinflammatory properties have been measured [32]. Of particular note, in an in vivo mouse model, orientin exerts antidepressantlike effects on mice, specifically by improving oxidative stress, neurotransmission, and neuroplasticity [33].…”
Section: Discussionmentioning
confidence: 99%